The Copernican Hypotheses Part 2 - Dersley, Stephen (Journal of Applied Cultural Studies, 2015)
The Copernicus constructed by Thomas S. Kuhn in The Copernican Revolution (1957) is a decidedly non-revolutionary astronomer who unwittingly ignited a conceptual revolution in the European worldview. Kuhn’s reading of Copernicus was crucial for his model of science as a deeply conservative discourse, which presented in The Structure of Scientific Revolutions (1962). This essay argues that Kuhn’s construction of Copernicus and depends on the suppression of the most radical aspects of Copernicus’ thinking, such as the assumptions of the Commentariolus (1509-14) and the conception of hypothesis of De Revolutionibus (1543). After comparing hypothetical thinking in the writings of Aristotle and Ptolemy, it is suggested that Copernicus’ conceptual breakthrough was enabled by his rigorous use of hypothetical thinking.